Morphology Engineering for High‐Performance and Multicolored Perovskite Light‐Emitting Diodes with Simple Device Structures. Issue 32 (8th July 2016) - Wang, Zhibin; Cheng, Tai; Wang, Fuzhi; Dai, Songyuan; Tan, Zhan'ao
Abstract : The film morphology is extremely significant for solution processed perovskite devices. Through fine morphology engineering without using any additives or further posttreatments, a full‐coverage and high quantum yield perovskite film has been achieved based on one‐step spin‐coating method. The morphologies and film characteristics of MAPbBr3 with different MABr:PbBr2 starting material ratios are in‐depth investigated by scanning electron microscopy, atomic force microscopy, X‐ray diffraction, photoluminescence, and time resolved photoluminescence. High performance organometal halide perovskite light‐emitting didoes (PeLEDs) based on simple device structure of indium tin oxide/poly(3, 4‐ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS)/perovskite/TPBi/Ca/Al are demonstrated. The green PeLED based on MAPbBr3 shows a maximum luminance of 8794 cd m −2 (at 7.3 V) and maximum current efficiency of 5.1 cd A −1 (at 5.1 V). Furthermore, a class of hybrid PeLEDs by adjusting the halide ratios of methylammonium lead halide (MAPb X 3, where X is Cl, Br, or I) are also demonstrated at room temperature. These mix‐halogenated PeLEDs show bright luminance (above 100 cd m − 2 ) with narrow and clean emission bands over the wide color gamut. Abstract : Multicolored perovskite light‐emitting diodes (PeLEDs) are fabricated via fine morphology engineering without any additives or further posttreatments. The green device reaches a maximum luminance of 8794 cd m −2 (at 7.3 V) and maximum current efficiency of 5.1 cd A −1 (at 5.1 V). Furthermore, high luminance (above 100 cd m −2 ) mix‐halogenated PeLEDs are also demonstrated.